A computational method for optimal design of the multi-tower heliostat field considering heliostats interactions. (1st July 2016) - Piroozmand, Pasha; Boroushaki, Mehrdad
Abstract: In multi-tower heliostat fields, although heliostats are capable of aiming at different receivers during the day, due to different orientations, neighboring heliostats might affect shading and blocking efficiency of each other reciprocally. In the proposed method of this paper, considering the mentioned effects and based on a group decision-making approach, each heliostat chooses the best receiver thus ensuring the highest possible instantaneous efficiency of the field. As a case study, this method is applied for the optimal design of a multi-tower field. Then, the field performance is simulated in a case where heliostats make decisions individually without considering the interactions. Finally, these results are compared with separated single tower fields' energy performance. Results of the case study show that, due to the high dependency on shading and blocking factor, the annual efficiency of the multi-tower field without considering the interactions is only slightly higher than the two separated single tower fields. However, using the proposed method, the optical performance of the multi-tower field improves and the annual efficiency of 54.58% is reachable, which is 0.21% higher than the case without considering the interactions and 0.26% higher than the separated single tower fields. Highlights: A new method for optimal design of multi-tower heliostat fields is presented. In the efficiency calculations, shading and blocking efficiency is considered. As a case study, a multi-tower field is optimally designed using the proposed method. The multi-tower fields' performance are analyzed and compared with single tower fields. The proposed method improves heliostats decision-making and the annual efficiency.